Teaching arts and science with the new social media - Wankel, Charles (Bingley, U.K. : Emerald, 2011)
This book will cover a wide range of approaches to applying social media in teaching arts and science courses. The first part of the book, SOCIAL LEARNING AND NETWORKING APPROACHES TO TEACHING ARTS & SCIENCE, will cover collaborative social media in writing courses, the use of wikis as a platform for co-creation of digital content, and powerful data sharing. Part two, SOCIAL MEDIA PEDAGOGIES FOR THE FUTURE OF ARTS & SCIENCE LEARNING, explores the expansive vistas enabled by these new technologies. The use of content posting in public social media forums as an enabler of critical reflection is considered, as will the use of social media to augment face-to-face meetings. The third part, LEARNING ARTS & SCIENCE IN THREE-DIMENSIONAL VIRTUAL WORLDS, will look to the opportunities and downsides of this immersive technology. Design recommendations for instructors will be put forth. Part four, BLOGGING AND MICROBLOGGING IN A NEW EPOCH OF TEACHING ARTS & SCIENCE, will look at a welter of applications and implications for teaching practices. For example, the use of Twitter as a sandbox where students share ideas before arriving in class or as back-channels to classes is explored.
New dimensions of communicating with students : introduction to teaching arts and science with the new social media / Charles Wankel -- Fostering meaning and community in writing courses via social media / James Schirmer -- Learning about media effects by building a wiki community : students' experiences and satisfaction / Jennie M. Hwang, Boris H.J.M. Brummans -- Facebook, 'friending,' and faculty-student communication / Lora Helvie-Mason -- How Twitter saved my literature class : a case study with discussion / Andy Jones -- Social learning with social media : expanding and extending the communication studies classroom / Robert Bodle -- Teaching social media skills to journalism students / Geoffrey Roth -- Unlocking the voice of the university : the convergence of course, content, delivery, and marketing through social media / Ryan Busch -- Understanding communication processes in a 3D online social virtual world / Aimee deNoyelles, Kay Kyeongju Seo -- Multi-user virtual environments for international classroom collaboration : practical approaches for teaching and learning in Second Life / Annie Jeffrey, Scott Grant, Howard M. Gregory -- Using multi-user virtual environments in tertiary teaching : lessons learned through the UQ religion bazaar project / Helen Farley -- Fostering an ecology of openness : the role of social media in public engagement at the Open University, UK / Linda Wilks, Nick Pearce -- Disconnect36 : a social experiment to teach students to shut down, turn off, and understand connectivity / Monica Flippin-Wynn, Natalie T.J. Tindall -- Is podcasting an effective resource for enhancing student learning? / Sheila Scutter -- Introducing students to micro-blogging through collaborative work : using Twitter to promote cross-university relationships and discussions / Tricia M. Farwell, Richard D. Waters -- Social media assemblages in digital humanities : from backchannel to Buzz / Alexander Reid -- Social media as a professional development tool : using blogs, microblogs, and social bookmarks to create personal learning networks / Corinne Weisgerber, Shannan H. Butler -- Micro-blogging and the higher education classroom : approaches and considerations / Gavan P.L. Watson.
Includes index.
Print version record
Keywords: Education -- Professional Development; Education -- General; Education; Curriculum planning & development; Internet in education; Social media